Tautai : Sāmoa, world history, and the life of Taʻisi O.F. Nelson - O'Brien, Patricia, 1969- (University of Hawaiʻi Press, 2017)
'Tautai' is the story of a man who came from the edge of a mighty empire and then challenged it at its very heart. This biography of Ta'isi O.F. Nelson chronicles the life of a man described as the 'archenemy' of New Zealand and its greater whole, the British Empire. He was Samoa's richest man who used his wealth and unique international access to further the Samoan cause and was financially ruined in the process.